高新技术的产业化及其在中国的运用 = The commercialization of high-technology and its application in China - 许泳 Xu, Yong (2010)
从高科技在发达国家发展的检讨，这项研究表明，高新技术的商品化能创造新产业，提升传统产业，加快经济增长。因此，这种知识的经济功能已被广泛接受世界各地的大多数国家正在作出巨大努力，以促进高科技商品化。 From review of the development of high-technology in the developed countries, This study shows that the commercialization of high technology can create new industries, upgrade traditional industries and accelerate the economy growth. Hence, this feature of knowledge economy has now been widely accepted all around the world and most of the countries are making great efforts to promote the commercialization of high-technology.